Can you hear the trees talking? : discovering the hidden life of the forest - Wohlleben, Peter, 1964-; Billinghurst, Jane, 1958- (Greystone Kids, 2019)
A global advocate for forests and our relationship with trees shares the mysteries and magic of the forest in language kids can understand. Includes quizzes and hands-on activities.